When is flow re-entrainment important for the flushing time in coastal reef systems?. (13th December 2020) - Winter, G.; Castelle, B.; Lowe, R.J.; Hansen, J.E.; McCall, R.
Abstract: The rates of water exchange between coastal reef systems and the surrounding ocean are key physical drivers of water quality and reef ecosystems. It is generally assumed that water exiting a reef system through reef channels is predominantly replaced by 'new' water from offshore. However, exiting water may also recirculate back into the reef system reducing the rate of exchange between the reef and the ocean, which has implications for reef water temperatures, nutrient fluxes and population connectivity. To quantify flow re-entrainment at a rocky reef site in southwestern Australia, flow patterns were measured with GPS-tracked drifters during a two-week field experiment. The field observations were extended via a set of idealized numerical experiments to determine the effect of variable oceanic forcing and reef geometry on flow re-entrainment. The observations demonstrate that re-entrainment can vary significantly and the numerical results support the hypothesis that re-entrainment increases with increasing offshore wave height, increasing alongshore currents outside of the reef, and decreasing reef channel spacing but is largely not impacted by reef roughness. Re-entrainment was correlated with a predictor variable R, which is a measure of wave forcing versus the total offshore flow cross-section, and alongshore currents outside the reef. For large values of R and strong alongshore currents, flow re-entrainment increases the effective flushing time by a factor of three or more. The results suggest that flow re-entrainment may be particularly important in small-scale reef systems or reefs exposed to an energetic wave climate and/or strong alongshore currents. Highlights: Flow re-entrainment varies within reefs and can greatly increase flushing times. Closely spaced channels, large waves and longshore currents increase re-entrainment. Large waves weaken the effect of longshore currents on re-entrainment and vice versa.